Management of Urban Development in The Southwest Region of the Adaptation to Climate Change - Anh, Pham Minh; Van Quan, Do (VNU Journal of Science: Policy and Management Studies, 2020)
Urban development management is a global trend, and an urgent requirement in Vietnam today. In recent years, urban development in the southwestern region along the trend of adaptation to climate change has received the attention of the Party and the State; at the same time achieve certain results. However, the management of urban development in the southwestern region adapting to climate change is still inadequate, requiring more robust, systematic and synchronized measures in the development process and urban management in the Southwest region.